2015
DOI: 10.1016/j.reprotox.2015.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal perchlorate, thiocyanate, and nitrate exposure with neonatal size and gestational age

Abstract: Background Perchlorate and similar anions compete with iodine for uptake into the thyroid by the sodium iodide symporter (NIS). This may restrict fetal growth via impaired thyroid hormone production. Methods We collected urine samples from 107 pregnant women and used linear regression to estimate differences in newborn size and gestational age associated with increases in perchlorate, thiocyanate, nitrate, and perchlorate equivalence concentrations (PEC; measure of total NIS inhibitor exposure). Results NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
2
5
2
Order By: Relevance
“…Our study was unable to confirm the association between maternal perchlorate exposure and offspring birthweight in the whole cohort as well as in the subgroup of male infants. This is in keeping with a previous study which also found no association between perchlorate exposure in pregnancy and offspring’s birthweight, birth length or gestational age at birth [ 22 ]. However, taken together, these observations highlight the need for further investigations to examine whether environmental exposure to perchlorate during pregnancy has adverse health outcomes beyond minor changes on maternal thyroid hormone levels.…”
Section: Discussionsupporting
confidence: 93%
“…Our study was unable to confirm the association between maternal perchlorate exposure and offspring birthweight in the whole cohort as well as in the subgroup of male infants. This is in keeping with a previous study which also found no association between perchlorate exposure in pregnancy and offspring’s birthweight, birth length or gestational age at birth [ 22 ]. However, taken together, these observations highlight the need for further investigations to examine whether environmental exposure to perchlorate during pregnancy has adverse health outcomes beyond minor changes on maternal thyroid hormone levels.…”
Section: Discussionsupporting
confidence: 93%
“…Although no direct correlation of perchlorate and these parameters was described, the increase in perchlorate, thiocyanate and urine nitrate concentrations was correlated with a slower waist and BMI increase. This contrasts with the results described above [124][125][126][127], where newborns were studied, but no dependence was found, or they were found only in boys or only for head circumference.…”
Section: Association Between Perchlorate Exposure and Children Gross contrasting
confidence: 99%
“…Moreover, studies conducted by Taylor et al [133] appear to confirm that the dependence of IQ decrease in three-yearold children was invariably upheld along with the increase in perchlorate in the urine of their mothers. Certainly, further studies and affirmations are required to describe the correlation of goitrogen exposure and the size of newborns, as also in this case, existing reports [124][125][126][127] do not allow for the formulation of unambiguous conclusions. In addition to the studies presented in the present review, perchlorate in human urine have also been found in China [8,140], in Haiti [141] and Kuwait [142] and in maternal milk in the USA [83,143] and in human blood in China [144].…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, in northern Chile, birthweights were similar in infants from cities with drinking water perchlorate concentrations of 113.9 µg/L (n=55 subjects), 5.82 µg/L (n=48), and below detection (n=55) although a large fraction of the subjects from the higher exposure city moved to and gave birth in the larger lower exposure city (30). In a recent study in New Jersey, maternal urinary perchlorate concentrations were not related to birthweight, although the sample size was small (n=107) and all subjects were recruited from a high risk pregnancy clinic (29). The study presented here is the first report of perchlorate exposure potentially altering birthweight, and the first to examine perchlorate and preterm birth.…”
Section: Discussionmentioning
confidence: 99%